1984
DOI: 10.1007/bf01407598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mixed neutron-gamma irradiation in vivo on the cell surfaces of murine blood cells

Abstract: For studies on cell membranes, mice were exposed to mixed neutron + gamma reactor-radiation in the range of total doses from 0.5 to 4.5 Gy. Changes in functional activity of plasma membranes of erythrocytes, platelets, and lymphocytes were followed by a lectin-binding technique at various intervals afterwards. The amount of 3H-concanavalin A bound to cells altered considerably during the 1st h after irradiation in all cell types. Lymphocytes and platelets, however, were more sensitive than erythrocytes as incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…This increased glucose uptake upon environmental stress can be considered as a general response of cells through changes in plasma membrane function. Alteration of the physiological conditions of membranes have also been shown in our earlier experiments in vitro on different cell cultures and blood cells exposed to ionizing radiation at relatively low doses (0.25-2.5 Gy), as detected by the binding of radiolabelled concanavalin A lectin to the cell surfaces (Köteles et al, 1976;Kubasova et al, 1981aKubasova et al, , 1981bKubasova et al, , 1984.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…This increased glucose uptake upon environmental stress can be considered as a general response of cells through changes in plasma membrane function. Alteration of the physiological conditions of membranes have also been shown in our earlier experiments in vitro on different cell cultures and blood cells exposed to ionizing radiation at relatively low doses (0.25-2.5 Gy), as detected by the binding of radiolabelled concanavalin A lectin to the cell surfaces (Köteles et al, 1976;Kubasova et al, 1981aKubasova et al, , 1981bKubasova et al, , 1984.…”
Section: Introductionsupporting
confidence: 61%
“…In spite of the membrane perturbation effect of ionizing radiation (Köteles et al, 1976;Kubasova et al, 1984), no alteration was found in glucose uptake by Calu-1 cells irradiated with 1 Gy and incubated either in the restrictive or the complete medium. It seems that the cell responses to physical or chemical factors are formed in a different manner in the restrictive and the complete medium.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 There is also evidence that irradiation‐induced alterations in membrane proteins involve reduction in lectin binding. 36 The relative contribution of protein versus lipid damage to radiopermeabilization of cell membranes remains to be defined and is perhaps cell‐type specific.…”
Section: Discussionmentioning
confidence: 99%